2016
DOI: 10.3803/enm.2016.31.2.292
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Diabetes Incidence in the Last Decade Based on Korean National Health Insurance Claims Data

Abstract: BackgroundEpidemiological data is useful to estimate the necessary manpower and resources used for disease control and prevention of prevalent chronic diseases. We aimed to evaluate the incidence of diabetes and identify its trends based on the claims data from the National Health Insurance Service database over the last decade.MethodsWe extracted claims data on diabetes as the principal and first additional diagnoses of National Health Insurance from January 2003 to December 2012. We investigated the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 14 publications
1
31
0
Order By: Relevance
“…From contemporary studies, the ageand sex-adjusted diabetes incidence rates among adults were 370 per 100,000 person-years in the United Kingdom [33], 398 per 100,000 person-years in Sweden [34], and 710 per 100,000 person-years in the US during the 2012-2014 period [35]. Over a comparable reporting period, the rates were 1,099 and 949 per 100,000 person-years in men and women in our study, 830 per 100,000 person-years in Korea [36], and 800 per 100,000 person-years in Taiwan [37]. Differences in methods used to capture incident cases and diagnostic intensities would have influenced the estimates.…”
Section: Incidence Of Type 2 Diabetes In Middle-aged To Older Adultssupporting
confidence: 56%
“…From contemporary studies, the ageand sex-adjusted diabetes incidence rates among adults were 370 per 100,000 person-years in the United Kingdom [33], 398 per 100,000 person-years in Sweden [34], and 710 per 100,000 person-years in the US during the 2012-2014 period [35]. Over a comparable reporting period, the rates were 1,099 and 949 per 100,000 person-years in men and women in our study, 830 per 100,000 person-years in Korea [36], and 800 per 100,000 person-years in Taiwan [37]. Differences in methods used to capture incident cases and diagnostic intensities would have influenced the estimates.…”
Section: Incidence Of Type 2 Diabetes In Middle-aged To Older Adultssupporting
confidence: 56%
“…The NHIS database is mandated by the Korean government. Therefore, the NHIS in Korea covers approximately 100% of the Korean population (~51 million) and all health‐care utilization information is registered in the comprehensive database operated by the Health Insurance and Review Agency . The NHIS computerized database provides data including all types of claim data as well as registries of rare incurable disease (RID) such as cancer.…”
Section: Methodsmentioning
confidence: 99%
“…The National Health Insurance Service (NHIS) is a governmental institution for health care insurance in Korea and provides a complete set of medical information on almost 97% of Korean citizens. Many studies have been conducted with the NHID, the feasibility of which for research on breast cancer survivors we previously reported …”
Section: Introductionmentioning
confidence: 99%
“…10,11 The National Health Insurance Service (NHIS) is a governmental institution for health care insurance in Korea and provides a complete set of medical information on almost 97% of Korean citizens. Many studies have been conducted with the NHID, 12,13 the feasibility of which for research on breast cancer survivors we previously reported. 14 This nationwide, retrospective study was aimed at investigating the incidence of late CHF more than 2 years after the breast cancer diagnosis in comparison with the general population and at assessing the risk factors for late CHF in breast cancer survivors.…”
Section: Introductionmentioning
confidence: 99%